A Corporate Tax Aggressiveness Influenced by CSR and Financial Ratios - Evi, Tiolina; Sasongko, Fajar (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
The purpose of this study is to investigate and analyze the relationship between corporate social responsibility, leverage, and company size and tax aggressiveness. Using the GRI-4 indicator with 91 items, the research examines corporate social responsibility as an independent variable. The debt-to-asset ratio is used to evaluate leverage, whereas the natural logarithm of total assets is utilized to evaluate the magnitude of a company. In this study, the dependent variable is tax aggressiveness, as measured by the Effective Tax Ratio (ETR). The annual reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2016 and 2020 were analyzed for this study. Types of research this is quantitative research. The sample selection procedure utilized a method of purposive sampling, yielding a total sample population of 157 businesses. However, only 54 businesses fulfilled the inclusion requirements for the study. The collected data was analyzed using version 26 of the SPSS software. According to the study's findings, corporate social responsibility has a substantial effect on tax aggressiveness. The study found no positive or statistically significant effects of leverage or company size on tax aggressiveness.